Developing media fire extinguishers light on vocational higher education - Suyitno, Suyitno; Danur Isnantyo, Fajar; Jatmoko, Dwi; Abdillah, Fuad; Mubarak, Ibnu (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to: 1) determine the development of cutting aids for lightweight fire extinguishers to improve learning outcomes in the Occupational Health and Safety course, 2) determine the feasibility of cutting a lightweight fire extinguisher to improve learning outcomes in the Health course and Occupational Safety, 3) know the effectiveness of cutting aids for lightweight fire extinguishers to improve learning outcomes in the Occupational Health and Safety course. The method used in this research is Research and Development (RnD ) using the Four-D device development model. In this development model consists of four stages namely: 1) Defining Phase, 2) Design Phase, 3) Development Phase, and 4) Disseminate Phase. Development is carried out based on several stages in accordance with the method used in this study. This development is appropriate to use after validation by media experts and material experts [20], [21]. This is reinforced by the trial of products and materials before the application of the research target has been carried out. The results of the application of the development carried out with a control class that does not use media get an average learning outcome of 66.80 and the experimental class that uses the media (carried out treatment) get a high average of learning outcomes of 84.80. Test tests get results 0, 00 which means less than 0.05, these results indicate that there are differences in learning outcomes. With this props cutting a lightweight fire extinguisher proven effective for improving learning outcomes in the course Health and Safety.